Business Survival: Competence of Micro, Small and Medium Enterprises - Rahayu Mardikaningsih; Elok Imroatul Azizah; Natasya Nafa Putri; Muhammad Nur Alfan; Muhammad Mas Davit Herman Rudiansyah (Journal of Social Science Studies (JOS3), 2022)
As a form of business that is able to survive during the financial crisis, Micro, Small and Medium Enterprises (MSMEs) have received the attention of all parties. In practice, MSME entrepreneurs have several obstacles other than capital. The large number of public interest in MSMEs creates competition for MSMEs that have similar business sectors. The low performance produced by MSMEs is due to the low quality of entrepreneurial competence. This research was conducted to determine the competencies required by MSMEs. The research method used in this research is descriptive qualitative. The sample of this research is 56 MSME entrepreneurs in the Tropodo village area, Waru sub-district, Sidoarjo district, East Java. The results of the study indicate that business actors already know their entrepreneurial competencies. Human relations competence is the most mastered competence and the lowest competence possessed is financial competence.